Energy, economic and environmental dynamic response characteristics of organic Rankine cycle (ORC) system under different driving cycles. (1st May 2022) - Ping, Xu; Yang, Fubin; Zhang, Hongguang; Xing, Chengda; Wang, Chongyao; Zhang, Wujie; Wang, Yan
Abstract: Internal combustion (IC) engine as the main power source of vehicle, its energy saving and emission reduction is of great significance to alleviate the energy crisis. Organic Rankine cycle (ORC) system has a good prospect in the field of waste heat recovery of IC engine. However, in the actual operation of the vehicle, the hysteresis time, time-varying and uncertainty of ORC system are more obvious. Moreover, under the influence of the fluctuation of IC engine and the hysteresis time of ORC system, the performance of the system is heavily dependent on the change of operating parameters. This paper firstly constructs four key models of power system, waste heat recovery system, chassis and driving cycle. Then, the driving cycle-based vehicle-ORC combined system model is proposed. From the perspective of thermodynamic performance, economic performance and environmental impact, the dynamic response characteristics of ORC system performance and operating parameters under real driving cycles are systematically evaluated. The performance of ORC system can be improved by 9.25–17.72% with the increase of the large speed gradient. The hysteresis time of ORC system is 16.6–144.3 s. Hysteresis time and performance degradation will become more serious with the superposition of decrease of the large speed gradient, low speed and idle speed. The hysteresis time under the influence of superposition is up to 150.4–295.3 s. There is also a 39.59–62.45% decline in performance. The analysis of dynamic characteristics of ORC system under complex real driving cycles can provide useful guidance for practical engineering application of vehicle ORC system. Highlights: A driving cycle-based vehicle-ORC combined system model is proposed. Results from strong fluctuation and large time-varying of driving cycles. Comparison of dynamic response characteristics of ORC system under real roads. Operating parameters and performance show strong coupling and transient pulsation.